Efektivitas Pelayanan Pembayaran Pajak Kendaraan Bermotor Berbasis Aplikasi Samsat Digital Nasional (Signal) Di Samsat Kota Padang - Meita Lefi Kurnia; Dola Riza; dwi Sutanto (Normative Jurnal Ilmiah Hukum, 2026)
Providing high-quality and superior public services is fundamental to the socioeconomic progress of society. SIGNAL, an innovation from the Indonesian National Police Traffic Corps (Korlantas Polri) for digital-based vehicle tax (PKB) payments, aims to improve PKB payment services, making them more modern, secure, and accessible. Regulation of the Republic of Indonesia National Police number 7 of 2021 concerning Registration and Identification of Motor Vehicles, article 61 states “Validation of STNK can be done: Manually on Samsat services; or Electronically on Samsat Online services. Based on these problems, this study examines How effective is PKB payments using the SIGNAL application based on aspects of convenience, speed and accuracy at Samsat Padang City?, what factors are driving and inhibiting the effectiveness of PKB payments through the SIGNAL application on compliance ofmotor vehicle taxpayers at Samsat Padang City? This study uses a research method with a descriptive empirical juridical approach, Data collection through library studies, interviews and observations, data processing using editing, coding and tabulating techniques. The results of the study show that the effectiveness of motor vehicle tax payment services based on the SIGNAL application at Samsat Padang City is illustrated through a comparison of digital tax payments with manual tax payments, with a ratio of 1: 25 of the number of private vehicles making tax payments in 2025. The number of SIGNAL usage for motor vehicle tax payments continues to show an increasing number. Several factors The driving factors include the need for service efficiency and flexibility; cost transparency and ease of delivery; local government support, strong synergy, and extensive outreach. Inhibiting factors include identity verification, missing NIK data synchronization, and failed vehicle registration; the time lag between successful payment and delivery (TBPKP); and a gap in technological understanding.